2011
DOI: 10.1182/blood-2011-05-356063
|View full text |Cite
|
Sign up to set email alerts
|

Cereblon expression is required for the antimyeloma activity of lenalidomide and pomalidomide

Abstract: The precise molecular mechanism of action and targets through which thalidomide and related immunomodulatory drugs (IMiDs) exert their antitumor effects remains unclear. We investigated the role of cereblon (CRBN), a primary teratogenic target of thalidomide, in the antimyeloma activity of IMiDs. CRBN depletion is initially cytotoxic to human myeloma cells, but surviving cells with stable CRBN depletion become highly resistant to both lenalidomide and pomalidomide, but not to the unrelated drugs bortezomib, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
510
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(548 citation statements)
references
References 19 publications
31
510
0
7
Order By: Relevance
“…CC-220 is structurally related to lenalidomide and pomalidomide that show antiproliferative and immunomodulatory effects on B and T cells (118,119). Similar to lenalidomide and pomalidomide, which bind to CRBN, a critical component of a ubiquitin E3 CRL4 CRBN complex (120,121), CC-220 binds to CRBN to promote recruitment of Ikaros and Aiolos to CRL4 CRBN and the subsequent enhancement of the ubiquitination and degradation of these transcription factors (55-57).…”
Section: Discussionmentioning
confidence: 99%
“…CC-220 is structurally related to lenalidomide and pomalidomide that show antiproliferative and immunomodulatory effects on B and T cells (118,119). Similar to lenalidomide and pomalidomide, which bind to CRBN, a critical component of a ubiquitin E3 CRL4 CRBN complex (120,121), CC-220 binds to CRBN to promote recruitment of Ikaros and Aiolos to CRL4 CRBN and the subsequent enhancement of the ubiquitination and degradation of these transcription factors (55-57).…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib is a proteasome inhbitor [39][40][41]; the mechanism of action of thalidomide and lenalidomide is unclear, but they are considered immunomodulatory agents [42] and may require cereblon (the putative primary teratogenic target for thalidomide) [43] expression for their anti-myeloma activity [44].…”
Section: Risk-adapted Therapymentioning
confidence: 99%
“…Stewart and colleagues first reported that RNAi knockdown of CRBN in multiple myeloma cells results in nearly complete cancellation of the anti-myeloma effects of IMiDs [23]. Furthermore, some patients who had become resistant to lenalidomide were found to have decreased expression of CRBN.…”
Section: Therapeutic Effects Of Imids Via Crbnmentioning
confidence: 99%